PESANTREN DI KALIMANTAN BARAT: Kajian Komparasi Tiga Pesantren dalam Perspektif Manajemen - Misdah, Misdah (Khatulistiwa, 2015)
This comparative study aims at investigating the management of three Islamic Boarding Schools in West Borneo i.e. Ushuluddin, Darul Ulum and Darussalam. Creswell theory of case study and Miles and Huberman theory including data reduction, data display, conclusion and verification have been employed for data analysis. Data collection for the study was carried out by means of interviews and observation towards several respondents i.e. the Principal, teachers, board coordinator, surrounding people and family. In addition, they also applied towards civil servants at the office of Ministry of Religion Affairs, along with theirdocumentation.The findings reveal that Ushuluddin and Darul Ulum are revivalist whereas Darussalam is adaptist in profile. Ushuluddin shares similar dynamic and socioculture to that of Malay i.e. charismatic and centralistic. Darul Ulum shares Maduranese and Javanese oriented while Darussalam applies multiculture.It can be recommended that Ushuluddin and Darul Ulum need to adjust their management with a view to broadening solidarity among boarders. It also applies to Darussalam in order to better result output with modern performance who can use all the skills they have to survive in multicultural society.